Farmer field schools - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Farmer field school is used as an approach to managing pests and diseases. It center around a 'living laboratory' where farmers are trained to identify insects and diseases and compare results on two subplots – one using conventional chemical pest control and the other using IPM. On the improved management plot, participants strive to improve ecosystem health by cutting pesticide use while increasing productivity through intensified management. Farmers experiment with a variety of techniques, such as weevil traps, different strains of potatoes, and targeted applications of lower toxicity pesticides.